Pemberdayaan Masyarakat Untuk Meningkatkan Kewaspadaan Terhadap Infeksi Strongyloides Stercoralis Di Desa Sukasari, Pulosari, Pandeglang, Banten - David Tjahyadi; Edy Parwanto; Sisca Sisca (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this PKM is to examine the rhabditiform larvae of Strongyloides stercoralis from soil samples in the yard of the residents of Sukasari, Pulosari, Pandeglang, Banten in 2022. The results of the examination which include the presence of rhabditiform larvae are used to explain to the residents. That is, so that residents understand the meaning of environmental cleanliness for their family members. Information about these rhabditiform larvae need to be known and understood that they can cause infectious diseases for their family members. The spread of rhabditiform larvae is related to habits that can cause autoinfection. Method of examination of soil samples to determine whether or not rhabditiform larvae of S. stercoralis. The result of this PKM showed that average length of S. stercoralis rhabditiform larvae is 81.13 μm. Ninety-five percent of the total samples contained S. stercoralis rhabditiform larvae. This means that the residents' yards, which are mostly soil, can be found with S. stercoralis rhabditiform larvae. The follow-up that needs to be done is to determine the prevalence of Strongyloidiasis, especially in elementary school age children and junior high school students.